PATHWAYS OF RECOGNITION OF FOREIGN ANTIGENS IN THE ADAPTIVE IMMUNE RESPONSE TO ALLOGENEIC ORGAN TRANSPLANTATION - A. S. Berkos; G. V. Nikolaev (Вестник трансплантологии и искусственных органов)
Immunological allograft rejection is based on the process of recognition of donor antigens by T-cell receptors. Antigens are generally represented by molecules of major hystocompatibility complex (MHC), expressed by the donor organ tissue cells. Immune response to allogeneic transplant in its activity is greatly higher than response to conventional infection wherein the basic mechanisms of recognition of infectious antigens and alloantigens seem to be similar. In this review we have analyzed three main pathways of recognition of alloantigens. Those pathways are differentiated by the nature of antigen presenting cells, kinetics and duration of its influence on the formation of alloimmunity: direct, indirect and semidirect. Establishing the relationship between mechanisms of allorecognition and manifestations of graft rejection is of great clinical importance.